2020
DOI: 10.1177/2058738420976309
|View full text |Cite
|
Sign up to set email alerts
|

LINC01018 and SMIM25 sponged miR-182-5p in endometriosis revealed by the ceRNA network construction

Abstract: The current study intended to explore the interaction of the long non-coding RNA (lncRNA), microRNA (miRNA), and messenger RNA (mRNA) under the background of competitive endogenous RNA (ceRNA) network in endometriosis (EMs). The differentially expressed miRNAs (DEmiRs), differentially expressed lncRNA (DELs), and differentially expressed genes (DEGs) between EMs ectopic (EC) and eutopic (EU) endometrium based on three RNA-sequencing datasets (GSE105765, GSE121406, and GSE105764) were identified, which were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…PELATON is a long noncoding RNA also known as long intergenic nonprotein coding RNA 1272 ( LINC01272 ), small integral membrane protein 25 ( SMIM25 ), or GC-related lncRNA 1 ( GCRL1 ). A handful of reports indicated that PELATON has dual functions as an oncogene or a suppressor gene by acting as a miRNA sponge ( 53 , 55 , 56 ). PELATON promotes metastasis of colorectal cancer or gastric cancer by targeting the miR-876 /ITGB2 axis ( 53 ) or miR-885- 3p/CDK4 ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…PELATON is a long noncoding RNA also known as long intergenic nonprotein coding RNA 1272 ( LINC01272 ), small integral membrane protein 25 ( SMIM25 ), or GC-related lncRNA 1 ( GCRL1 ). A handful of reports indicated that PELATON has dual functions as an oncogene or a suppressor gene by acting as a miRNA sponge ( 53 , 55 , 56 ). PELATON promotes metastasis of colorectal cancer or gastric cancer by targeting the miR-876 /ITGB2 axis ( 53 ) or miR-885- 3p/CDK4 ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these differentially expressed genes, the top four down-regulated lncRNAs were SMIM25, FENDRR, SFTA1P, and LINC01936 ( Table 2 ) and the top four up-regulated ones were LINC01133, CASC9, SOX21-AS1, and ESRG ( Table 3 ). After searching the literatures, we found that seven genes, except for LINC01936, were all contributed to the development of lung cancer by several pathways ( Chang et al, 2020 ; Gao et al, 2019 ; Jafari et al, 2022 ; Jiang et al, 2020 ; Ning et al, 2021 ; Wang et al, 2021a ; Xiong et al, 2019 ). Due to this, LINC01936 was used for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence supports the notion that miRNA can complement and bind to target genes and directly cut mRNA, so as to regulate the level of target mRNA[ 48 , 49 ]. The underlying mechanism for the role of miRNA-182-5p was further examined herein.…”
Section: Discussionmentioning
confidence: 96%